The Causal Relationship Between Blood Lipids and Systemic Lupus Erythematosus Risk: A Bidirectional Two-Sample Mendelian Randomization Study - Wang, Mingzhu; Huang, Shuo; Lin, Xiaoying; Wen, Chengping; He, Zhixing; Huang, Lin (Frontiers in Genetics, 2022)
Background: Although observational studies have demonstrated that blood lipids were associated with systemic lupus erythematosus (SLE), the causality of this association remains elusive as traditional observational studies were prone to confounding and reverse causality biases. Here, this study attempted to reveal the potential causal link between SLE and the levels of four blood lipids (HDL cholesterol, LDL cholesterol, TG, and TC). Methods: Bidirectional two-sample Mendelian randomization (MR) was employed to explore the unconfounded causal associations between the four blood lipids and SLE. In addition, regression-based Multivariate MR (MVMR) to quantify the possible mediation effects of blood lipids on SLE. After a rigorous evaluation of the quality of studies, the single-nucleotide polymorphisms (SNPs) associated with the four blood lipids were selected from the Global Lipids Genetic Consortium (GLGC) consisted of 188,577 individuals of European ancestry, and the SNPs related to SLE were selected from a large-scale genome-wide association study (GWAS) database named IEU GWAS. Subsequently, MR analyses were conducted with inverse-variance weighted (IVW), weighted median, weighted mode, simple mode, and MR-Egger regression. Sensitivity analyses were performed to verify whether heterogeneity and pleiotropy led to bias in the MR results. Results: Bidirectional two-sample MR results demonstrated that there was no significant causal association between SLE and the four blood lipids (When setting SLE as outcome, HDL cholesterol and SLE, IVW OR: 1.32, 95% CI: 1.05∼1.66, p = 1.78E-02; LDL cholesterol and SLE, IVW OR: 1.26, 95% CI: 1.04∼1.53, p = 2.04E-02; TG and SLE, IVW OR: 1.04, 95% CI: 0.71∼1.51, p = 8.44E-01; TC and SLE, IVW OR: 1.07, 95% CI: 0.89∼1.29, p = 4.42E-01; When setting SLE as exposure, SLE and HDL cholesterol, IVW OR: 1.00, 95% CI: 0.99∼1.01, p = 9.51E-01; SLE and LDL cholesterol, IVW OR: 0.99, 95% CI: 0.98∼1.00, p = 3.14E-01; SLE and TG, IVW OR: 0.99, 95% CI: 0.98∼1.00, p = 1.30E-02; SLE and TC, IVW OR: 0.99, 95% CI: 0.98∼1.00, p = 1.56E-01). Our MVMR analysis also provided little evidence that genetically determined lipid traits were significantly associated with the risk of SLE (HDL cholesterol and SLE, p = 9.63E-02; LDL cholesterol and SLE, p = 9.63E-02; TG and SLE, p = 8.44E-01; TC and SLE, p = 4.42E-01). Conclusion: In conclusion, these data provide evidence that genetic changes in lipid traits are not significantly associated with SLE risk in the European population.